Compression resistance of concretes with blast furnace slag. Re-visited state-of-the-art - Cabrera-Madrid, J. A.; Escalante-García, J. I.; Castro-Borges, P. (Revista ALCONPAT, 2016)
A state-of-the-art revision of the BFS-PC cementing system was done, emphasizing its effect on the mechanical compressive strength of the concrete. The use of the cementing characteristics of the BFS with high levels of replacements is viable, making it possible to improve the compressive strength, and in some cases, the resistance to the corrosion of the steel; said improvement will depend on the amount of BFS and on the exposure environment of the concrete. In this work, the replacements of BFS were confirmed as beneficial, up to 70% in humid microclimates or marine environments, and up to 50% in environments susceptible to carbonation. In these ranges, higher replacement efficiency with regard to resistance to compression can be achieved. Keywords: slag; carbonation; industrial byproduct; and corrosion.